Mode switching using optically induced long-period gratings: a theoretical analysis - Fernandes, Gil M. (2021)
We show that optically induced long-period grating (OLPG) is a particular case of inter-modal Bragg-scattering four-wave mixing (BS-FWM). To carry out such analysis, a vector model for the inter-modal BS-FWM was proposed and further tailored to investigate the energy transfer induced by OLPGs. Both processes, BS-FWM and OLPGs, have been proposed for in-line all-optical mode switching in transmission systems with space-division multiplexing (SDM). In this scope, we demonstrate that the bandwidth of OLPGs is larger than the BS-FWM. Furthermore, we show that OLPG-based mode switching can take place in two windows, if both pump beams are launched near the zero value of the differential mode-group delay, and the central wavelength and the bandwidth of such windows can be tuned by properly adjusting the wavelength and the optical power of the pump beams.